How to development of conceptual understanding using virtual laboratories among second-year secondary school students - Hamdi, Abdulaziz Mohammed (Journal of Curriculum and Teaching Methodology, 2024)
The current research aimed to reveal How to development of conceptual understanding using virtual laboratories among second-year secondary school students. To achieve the research goal the researcher used the procedural research approach. The researcher used two qualitative tools: observation and open questions. The data was analyzed using an open coding method. The results showed that the use of virtual laboratories had an impact on developing conceptual understanding through four aspects: Explanation or clarification, interpretation, application, and self-knowledge. This research contributed to developing the researcher’s teaching performance and increasing her conviction about the impact of using virtual laboratories in developing conceptual understanding. The current research recommended holding courses and training programs to train physics teachers to use virtual laboratories during the teaching process, Providing the Internet and organizing the study schedule. In conclusion, this research presented suggestions for conducting similar research that includes other variables.